Eat for life : the Food and Nutrition Board's guide to reducing your risk of chronic disease - Woteki, Catherine E.; Thomas, Paul R., 1953- (National Academy Press, 1992)
Gives guidelines for a dietary plan to reduce the risk of diet-related chronic diseases.
Based on: Diet and health / Committee on Diet and Health, Food and Nutrition Board, Committee on Life Sciences, National Research Council.
Keywords: Nutrition.; Chronic diseases -- Prevention.; Chronic diseases.; Diet in disease.; Chronic Disease; Diet; Nutritional Physiological Phenomena; Maladies chroniques.; Régimes alimentaires.; HEALTH & FITNESS -- Nutrition.; HEALTH & FITNESS -- Diets.; MEDICAL -- Nutrition.; MEDICAL -- Nursing -- Nutrition.; HEALTH & FITNESS -- Food Content Guides.; Diet in disease; Chronic diseases; Chronic diseases -- Prevention; Nutrition